AFETIVIDADE NOS PROCESSOS DE ENSINO E APRENDIZAGEM: UM ESTUDO COM PROFESSORES DOS CURSOS DE TERAPIA OCUPACIONAL NO INTERIOR DO ESTADO DO RIO GRANDE DO SUL - Silva, Eliane Caldas da (2019)
The teaching-learning process is increasingly as subject of studies and debates, motivated by the constant changes in society. For this reason, this research aims investigate what are the Occupational Therapy professors perceptions about the affectivity in their teaching practices, since affectivity is a vital component for the teaching process and that allows the mediation of knowledge. In order to reach this objective, an empirical and exploratory research was carried out, with a qualitative approach, in two universities in the interior of Rio Grande do Sul, with the participation of six professors. Subsequently their speesches were grouped by similarities in order to allow a analysis content, in which it was found that even though they did not have masterd of the concept of affectivity, the teachers used it in their practices. The results obtained in this research are presented in two articles entitled: Professorss' perception about affectivity in Higher Education in a Health course; The importance of affectiveness in interpersonal relations in the occupational therapy teaching practice. Is expected that this research motivates professors to familiarize about the concept of affectivity, so that their teaching practices become even more profitable, as well as the interpersonal professor-student relations. As well it is expected that this research will serve as a starting point for further studies about teaching practices in Occupational Therapy courses.